A molecular perspective for the use of type IV tyrosine kinase inhibitors as anticancer therapeutics. Issue 3 (March 2022) - Das, Rudradip; Choithramani, Asmita; Shard, Amit
Graphical abstract: Highlights: Tyrosine kinase type IV inhibitors are the least-explored type. Type IV inhibitors act at the transmembrane and cytoplasmic level. Binding pockets of the main inhibitors and their modes of action are discussed in detail. Abstract: Tyrosine kinases are enzymes that can transfer a phosphate group from ATP to a specific protein tyrosine, serine or threonine residue within a cell, operating as a switch that can turn 'on' and 'off' causing different physiological alterations in the body. Mutated kinases have been shown to display an equilibrium shift toward the activated state. Types I–III have been studied intensively leading to drugs like imatinib (type II), cobimetinib (type III), among others. It is the same scenario for types V–VII; however, there is a lacuna in information regarding type IV inhibitors, although recently some advances have surfaced. This review aims to accumulate the knowledge gained so far about type IV inhibitors.